KARAKTERISTIK DAN NILAI SUN PROTECTING FACTOR (SPF) KITOSAN DARI TULANG SOTONG (Sephia officinalis) - Ika Ristia Rahman; Athiah Masykuroh (Jurnal Insan Farmasi Indonesia, 2020)
Cuttlefish (sepia officinalis) have internal shells commonly called cuttlebones which produce more chitin than shrimp shells and crab skins. The purpose of this study was to determine the characteristics of chitosan from cuttlebone including the degree of deacetylation, water content, solubility, organoleptic test (color, odor, texture) as well as testing the value of chitosan protecting the sun protection factor. Chitosan is made in 3 stages, namely deproteination, demineralization, and deacetylation. Deproteination with 4% NaOH at 100 ° C for 60 minutes. Demineralization at room temperature using 1M HCl solution for 120 minutes. Deacetylation using 50% NaOH concentration at 100 ° C for 60 minutes. Chitosan characterization includes the degree of deacetylation, moisture content, solubility, organoleptic test (color, odor, texture). Testing the value of sun protection factor using a UV-VIS spectrophotometer read at wavelengths from 290 to 320 nm. Characteristics of chitosan produced according to chitosan standards used in industry with a deacetylation rate of 71%, yield 31%, moisture content of 0.93%, soluble in acetic acid2% solution, white odorless and powdery. Chitosan with a concentration of 3% gives the value of sun protecting factor 9 as a potential sunscreen that provides maximum protection power.